A (não) extração do objeto a na psicose: algumas notas sobre o Homem dos lobos - Virginia Lucia Souto Maior Sanabio (2009)
This paper investigates the Freudian clinical case known as The Man of the Wolves. The case opens a vast field of discussion by presenting a clinical polymorphism; however, our survey limits itself to the discussion of the relation of this subject to the pulsating object that, in the Lacan theory, deals with a notion of pleasure under the form of the a object. For the psychotic subject there was not an extraction of the a object; the initial advent of becoming subject is in a confused state instead of the Other, i.e. the distinction interior/exterior, in/out, I/other is blotted out. In order to discuss this theme our survey uses the topology, the psychoanalysis and the phenomenology of perception of Maurice Merleau-Ponty.